Structural perspectives on H2S homeostasis. (December 2021) - Landry, Aaron P.; Roman, Joseph; Banerjee, Ruma
Abstract: The enzymes involved in H2 S homeostasis regulate its production from sulfur-containing amino acids and its oxidation to thiosulfate and sulfate. Two gatekeepers in this homeostatic circuit are cystathionine beta-synthase, which commits homocysteine to cysteine, and sulfide quinone oxidoreductase, which commits H2 S to oxidation via a mitochondrial pathway. Inborn errors at either locus affect sulfur metabolism, increasing homocysteine-derived H2 S synthesis in the case of CBS deficiency and reducing complex IV activity in the case of SQOR deficiency. In this review, we focus on structural perspectives on the reaction mechanisms and regulation of these two enzymes, which are key to understanding H2 S homeostasis in health and its dysregulation and potential targeting in disease.